Application of 3D Fast Spin-Echo T1 Black-Blood Imaging in the Diagnosis and Prognostic Prediction of Patients with Leptomeningeal Carcinomatosis - Oh, J. (AJNR Am J Neuroradiol, 2018)
BACKGROUND AND PURPOSE: Contrast-enhanced 3D fast spin-echo T1 black-blood imaging selectively suppresses the signal of blood flow and could provide a higher contrast-to-noise ratio compared with contrast-enhanced 3D ultrafast gradient recalled echo (contrast-enhanced gradient recalled echo) and 2D spin-echo T1WI (contrast-enhanced spin-echo). The purpose of our study was to evaluate whether black-blood imaging can improve the diagnostic accuracy for leptomeningeal carcinomatosis compared with contrast-enhanced gradient recalled-echo and contrast-enhanced spin-echo and, furthermore, to determine whether the grade of leptomeningeal carcinomatosis evaluated on black-blood imaging is a significant predictor of progression-free survival. MATERIALS AND METHODS: Leptomeningeal carcinomatosis (n = 78) and healthy (n = 31) groups were enrolled. Contrast-enhanced gradient recalled-echo, contrast-enhanced spin-echo, and black-blood imaging were separately reviewed, and a diagnostic rating (positive, indeterminate, or negative) and grading of leptomeningeal carcinomatosis were assigned. The diagnostic accuracies of the 3 imaging sequences were compared in terms of leptomeningeal carcinomatosis detection. The Kaplan-Meier and the Cox proportional hazards model analyses were performed to determine the relationship between the leptomeningeal carcinomatosis grade evaluated on black-blood imaging and progression-free survival. RESULTS: Black-blood imaging showed a significantly higher sensitivity (97.43%) than contrast-enhanced gradient recalled-echo (64.1%) and contrast-enhanced spin-echo (66.67%) (P < .05). In terms of specificities, we did not find any significant differences among contrast-enhanced gradient recalled-echo (90.32%), contrast-enhanced spin-echo (90.32%), and black-blood imaging (96.77%) (P > .05). A Cox proportional hazards model identified the time to metastasis, Karnofsky Performance Scale status, and a combination of the leptomeningeal carcinomatosis grade with a linear pattern as independent predictors of progression-free survival (P < .05). CONCLUSIONS: Black-blood imaging can improve the diagnostic accuracy and predict progression-free survival in patients with leptomeningeal carcinomatosis.